MOTIVASI DAN KENDALA WISATAWAN WISATA MINAT KHUSUS TREKKING DI GUNUNG RINJANI - Moh. Habibi Azhari; Achlan Fahlevi Royanow; Jumraidin, Jumraidin (Bajang Institute, 2024)
This study examines the motivations and challenges faced by tourists in the special interest trekking tourism on Mount Rinjani. Through tourist interviews, it was found that their primary motivations include natural beauty, physical challenge, relaxation, and opportunities for socializing. Tourists are attracted by stunning views such as sunrise and sunset, as well as unique flora and fauna present in Rinjani. However, they face various challenges, including extreme weather, physical and mental preparedness, lack of basic facilities such as toilets and water sources, and limited information and guidance for trekking. To enhance the trekking experience on Mount Rinjani, it is recommended that managers improve and add basic facilities, provide more comprehensive information, and better train local guides. Additionally, better environmental management is necessary, including more effective waste management efforts and limiting the number of daily trekkers. With these measures, it is hoped that Mount Rinjani can become a more comfortable, safe, and sustainable trekking destination, while remaining attractive to tourists from various backgrounds